"He came back a changed man": The popularity and influence of policy tourism. Issue 3 (13th November 2018) - Baker, Tom; McGuirk, Pauline
Abstract : Why does policy tourism remain a popular and influential method of policy learning and mobility in an age of information abundance? Framed by a case study of homelessness policy tourism to New York City, this paper suggests that policy tourism remains popular because it allows for: (1) thinking outside the everyday strictures of the bureaucratic workplace; (2) the development of associational bonds between policy tourists, and between tourists and hosts; (3) the verification of information; and (4) the legitimation of decisions/positions. Noting the powerful influence that tourist encounters have on policy tourists, the paper then discusses the production of authenticity. The paper calls for greater attention to the active and affective production of authenticity as a means to better understand policy tourism and its significant effect on policy learning and mobility. Abstract : Why does policy tourism remain a popular and influential method of policy learning and mobility in an age of information abundance? The paper calls for greater attention to the active and affective production of authenticity as a means to better understand the effect of policy tourism.